Restructuring Sharing Time for English Learners and Their Parents. (3rd February 2015) - Protacio, Maria Selena; Edwards, Patricia A.
Abstract In this article, the authors discuss how sharing time, a staple classroom practice in primary grade classrooms, was modified to increase involvement among parents of ELLs. The authors discuss the benefits of modifying sharing time to focus on specific cultural artifacts from ELLs' native culture. This modification allowed for meaningful conversations and planning to occur between ELLs and their parents. The sharing time presentation also increased the interest and knowledge of the ELLs and their classmates about their native culture.